ANALISIS YURIDIS MENGENAI HUKUMAN KEBIRI KIMIA KEPADA PELAKU YANG MELAKUKAN KEKERASAN SEKSUAL TERHADAP ANAK (Studi Putusan Nomor. 859/Pid.Sus/2023/Pn.Bjm) - Novita Sari Ayu Simanjuntak; Marlina Marlina; Yati Sharfina Desiandri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract:Handlingofsexualviolenceagainstchildren in thecriminallawsystemstilltendstohighlightthecrimefromtheperspectiveoftheperpetrator. Ofcourse, itis not balancediftheperspectiveofthechild as a victimisignored. The Indonesian government has imposedchemicalcastration as a breakthrough in minimizingtheincreasing level ofsexualviolenceagainstchildren. Basedontheprovisionsof Law Number. 17 of 2016 concerningtheprotectionofchildren in theimplementationofchemicalcastration, doctors are mandatedtocarryoutchemicalcastrationontheperpetrators. Thisraisesproblemsrelatedtoaspectsof human rightsandmedicalethics. ThiscanbeseenfromDecisionNumber. 859/Pid.Sus/2023/Pn.Bjmwhichsentencedthedefendanttoadditionalchemicalcastration. The resultsofthe study onDecisionNumber. 859/Pid.Sus/2023/Pn.Bjm. The judgestatedthatthedefendantwasproventohavecommittedsexualviolenceagainst a 13-year-old childvictim, thedefendant as aneducator. However, theadditionalpunishmentimposedonthedefendant in theformofchemicalcastrationisconsideredcontroversial, whichincreasesthepunishmentfortheperpetrator. The ambiguity in thetechnicalimplementation, thepotentialforchanges in theperpetrator'sconditionduringdetention, theunpreparednessoftheimplementinginstitution, andethicalconflictswithmedicalpersonnel. Thiscausestheriskof legal uncertaintyandpotential human rightsviolationsfortheperpetrator, whoserightsmuststillbeprotectedduringthe legal process in implementingsanctions. Withoutignoringtheprinciplesofjusticeandhumanity in implementingthechemicalcastrationpunishment.  Keyword:Sexual Violence, Children, Punishment, Chemical Castration  Abstrak: Penanganan kekerasan seksual terhadap anak dalam sistem hukum pidana masih cenderung menyoroti kejahatan dari sudut pandang pelaku. Tentu saja tidak seimbang jika sudut pandang terhadap anak sebagai korban diabaikan. Pemerintah Indonesia memberlakukan hukuman kebiri kimia sebagai trobosan dalam meminimalisir tingkat kejahatan kekerasan seksual terhadap anak yang semakin meningkat. Berdasarkan pengaturan Undang-Undang Nomor.17 Tahun 2016 tentang perlindungan anak dalam pelaksanaan hukuman kebiri kimia memberikan amanat dokter untuk melaksanakan hukuman kebiri kimia kepada pelaku. Menimbulkan problematika terkait aspek hak asasi manusia dan etika kedokteran. Dapat dilihat dari Putusan Nomor. 859/Pid.Sus/2023/Pn.Bjm yang menjatuhkan terdakwa hukuman tambahan kebiri kimia. Hasil penelitian terhadap Putusan Nomor. 859/Pid.Sus/2023/Pn.Bjm. Hakim menyatakan bahwa terdakwa terbukti melakukan kekerasan seksual terhadap anak korban 13 tahun, terdakwa sebagai tenaga pendidik. Namun hukuman tambahan yang dijatuhi kepada terdakwa berupa kebiri kimia dianggap kontroversi yang memperberat hukuman bagi pelaku.Ketidakjelasan dalam teknis pelaksanaan, potensi perubahan kondisi pelaku selama masa tahanan, ketidaksiapan institusi pelaksana, serta konflik etika dengan tenaga medis. Hal ini menyebabkan risiko ketidakpastian hukum dan potensi pelanggaran hak asasi manusia bagi pelaku, yang tetap harus dilindungi hak-haknya selama proses hukum dalam pelaksanaa sanksi. Tanpa mengabaikan prinsip keadilan dan kemanusiaan dalam menerapkan hukuman kebiri kimia tersebut.  Kata kunci: Kekerasan Seksual, Anak, Hukuman, Kebiri Kimia